Fatty acid profiles of migrating female silver eel from Mediterranean coastal lagoons as integrative descriptors of spawners biological quality - Capoccioni F.; Conto M.; Failla S.; Cataudella S.; Ciccotti E. (Estuarine, Coastal and Shelf Science, 2018)
The present study analyzed the lipid content and fatty acid profiles of European silver eels from Mediterranean lagoons, to interrogate the ecology and biology of eel, a panmictic species well represented in the region, with particular reference to breeder quality. Lagoons are coastal waterbodies included in transitional waters, sharing with these ecosystems, that include also brackish wetlands and river mouths, the characteristic of being influenced both by sea and continental waters. In the Mediterranean area these highly productive ecosystems, that also support a rich specific biodiversity, have a great relevance in relation to their great extent and the human and historical dimension, since they have long been exploited for their natural resources, especially for fishing. Eel collection was carried out in nine Italian lagoons typically representing these habitats, and two inland water habitats (a river and a lake) were added for comparison. Female silver eel muscle tissue revealed a mean lipid content significantly above the threshold considered necessary to provide the cue to trigger physiological reproductive changes for this species, in all the sampling sites irrespective of their typology. This emphasises the importance of Mediterranean coastal lagoons as habitats contributing to the eel oceanic migration, providing a significant share of spawning-stock biomass, both in terms of quality of the breeders and of their fitness to perform migration. Whereas the overall lipid content was similar among sites, the nine local populations differed in their fatty acid signatures. Thus, FA signatures might be proposed as integrative descriptors of eel spawner biological quality since they easily are able to differentiate among silver eel local stocks. Growth rates and body condition indices were strongly positively correlated to n-3:n-6 and DHA:EPA ratios in silver eels ready-to-migrate from the studied locations. This demonstrates that distinct PUFA, exclusively obtained through diet, are correlated with crucial ...